Impact of Frontline Demonstration on Indian Mustard through Improved Technology - Shishir Kumar* Yogesh Chandra Srivastava; Ameesh John Stephen (Indian Journal of Extension Education, 2018)
Indian mustard (Brassica juncea L.) is a major oilseed crop of Uttar Pradesh. It is also one of the important oilseed crops of Eastern Uttar Pradesh. However, its productivity is very low in the district of eastern Uttar Pradesh compared to other districts of Uttar Pradesh. The Directorate of Extension SHIATS, Allahabad has carried out 21 frontline demonstrations on Indian mustard covering an area of 7 ha. of farmers field in 7 districts (Allahabad, Kaushambi, Fatehpur, Pratapgarh, Mirzapur, Sonebhadra & Bhadohi) in 2015 & 2016 to exhibit latest production technologies and compared it with farmer’s practice. An attempt has also been made to know the productivity of frontline demonstrations and the adoption of latest production technologies by the 21 FLD farmers and 21 non-FLD farmers. FLD farmers and non FLD farmers were randomly selected from FLD villages. The results were compared between FLD plots and control plots. The results revealed that improved technologies of mustard enhanced yield from 14.32q/ha to 18.62 q/ha in frontline demonstrations. The percentage of increase in yield ranges from 17.77 to 31.14. The extension gap and technology gap were recorded ranging between 2.68-3.77 q/ha and 1.38-5.68 q/ha, respectively. The technology index ranged from 6.90 % to 22.40 %. The results indicated that the FLD was effective in changing attitude, knowledge and adoption of improved technologies of mustard and ultimately in obtaining sustain income.